2016
DOI: 10.1007/s40436-016-0160-7
|View full text |Cite
|
Sign up to set email alerts
|

Experimental characterization of Ti6Al4V T joints welded through linear friction welding technique: microstructure and NDE

Abstract: Linear friction welding (LFW) is an innovative solid-state welding technique that allows to manufacture joints with high mechanical properties. This technology has various applications in the aerospace field; in particular it is used to weld massive structural components made of Ti6Al4V. This paper deals with the experimental study of Ti6Al4V T-joints welded through LFW, with particular focus on the effectiveness of ultrasonic control in detecting and distinguishing welding defects within the joints. Aiming to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(2 citation statements)
references
References 30 publications
0
2
0
Order By: Relevance
“…porosity, hot cracking, solidification crack and segregation, is minimized in this LFW method [33][34] . Astarita et al [35] reported microporosity and kissing bond defect when Titanium is subjected to the LFW method.…”
Section: Defect and Microstructure In Linear Friction Weldingmentioning
confidence: 99%
“…porosity, hot cracking, solidification crack and segregation, is minimized in this LFW method [33][34] . Astarita et al [35] reported microporosity and kissing bond defect when Titanium is subjected to the LFW method.…”
Section: Defect and Microstructure In Linear Friction Weldingmentioning
confidence: 99%
“…They investigated the effect of various parameters on FSW such as different welding speeds, tool temperatures, and forces. Astarita et al studied Ti6Al4V T joints welded with linear friction welding method [5]. They concluded that ultrasonic control for detecting and identifying defects is effective.…”
Section: Introductionmentioning
confidence: 99%